Evolution of restricted bulboventricular foramen in double inlet left ventricle and ventriculoarterial discordance - Sarisoy, Ozlem; Ayabakan, Canan; Tokel, Kursad; Akdeniz, Osman; Turkoz, Riza; Vuran, Can; Ozker, Emre (Turkish Soc Cardiology, 2012)
[Abstract Not Available]
Çift girişli sol ventrikül, ventriküloarteriyel diskordansı olan olguların izleminde restriktif bulboventriküler foramen gelişimi
Keywords: Pulmonary-Artery; Univentricular Heart; Subaortic Stenosis; Size